Cooperative strategy - Nielsen, Richard P. (Strategic Management Journal, 1988)
Abstract This article develops a classification scheme for mutual gain cooperative strategies between and among different organizations. The cooperative strategies considered are pool, exchange, de‐escalate, and experiment/contingency. These cooperative strategies are considered in four types of game/market environmental life cycle situations: positive‐sum growth, zero‐sum mature, negative‐sum decline, and transformable to positive‐sum growth. Cases from domestic and international business, nonprofit and government organizations are illustrated. Literature examples from strategic management, evolutionary biology, game theory and ecosystems theory are synthesized and used as foundation and explanation. Positive and negative public policy implications of cooperative strategy are also considered. In most, but not all, cases, cooperative strategy appears to improve value‐added efficiency in a wide variety of environments and situations.